The effect of distribution supply fertilizer on rice production improvement in Gorontalo City - Amir Halid; Heldy Vanni Alam; Mohamad Hamdi H. Payuyu (Program Magister Ilmu Ekonomi Pascasarjana Universitas Jambi, 2018)
The purposes of this research are to: 1) analyze the distribution of subsidized fertilizer in Gorontalo City, 2) analyze the distribution of subsidized fertilizers partially (right price, right amount, and time) to increase rice production in Gorontalo City. The study conducted in Gorontalo City with a sample number of 95 farmers. The research method used is survey method. Data analysis used is multiple linear regression analysis. The results showed that there are two distributors fertilizer in Gorontalo City is PT. Indonesian Trade Company (PT PPI) and Indonesian Trade Cooperative (KPI), and 5 authorized retailers which are distributing subsidized fertilizer is Kios Tani Lestari, Anugerah Tani Kios, Saprodi Tani Kios, Cahaya Tani Kios and Bunga Tani Kios. PT. PPI is responsible for distributing NPK, SP36 and ZA fertilizers while KPI is responsible for the distribution of Urea fertilizer. Distribution of subsidized fertilizer on rice farming simultaneously have a positive and real effect on increasing rice production, while partially that have positive and real influence that is Right price, Right amount and time to increase rice production